Wikipetcia Atikamekw Nehiromowin: Wikipedia in Indigenous Languages - Béland, Jean-Philippe (Septentrio Conference Series, 2021)
This presentation is to present the "Atikamekw Project" led in Canada with the Atikamekw First Nation to create the Wikipetcia Atikamekw Nehiromowin, the Wikipedia in Atikamekw language, as well as improving the presence of the Atikamekw knowledge, culture and language on Wikimedia projects by uploading photographs, archives, and videos on Wikimedia Commons, using Lingua Libre to add Atikamekw words in the Wiktionaries, etc. This project is led by the Atikamekw community with the support of Wikimedia Canada. The Metapeckeka WikiClub, the WikiClub of the Atikamekw Community of Manawan, is one of the most active WikiClubs in Canada despite being in a remote location and having a small population. We will share how Wikimedia Canada is supporting the project to empower the Atikamekw community in creating and growing the Wikipedia in their language.